Reconstruction of the Superficial Palmar Arch Using the Subscapular Arterial System - Anna K. Steve, MD; Véronique Doucet, MEng, MD; Danielle Dumestre, MD; Farrah M. K. Yau, MD, FRCSC (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. Hypothenar hammer syndrome is a rare entity warranting urgent exploration of the ulnar artery if signs of critical digital ischemia are present. To the authors’ knowledge and based on review of the relevant literature, this case report is the first to describe the harvest of the subscapular arterial system for reconstruction of an extensive arterial defect involving the ulnar artery, superficial palmar arch, and associated branches for a case of hypothenar hammer syndrome. The patient presented with an ischemic and exquisitely painful fourth digit. After undergoing the aforementioned reconstruction, all digits were subsequently well perfused with normal capillary refill, color, warmth, and sensation. A strong ulnar pulse was palpated at the volar wrist crease. Patency of the interposition graft was verified by CT angiography (6 weeks postoperatively) and Doppler ultrasound (4 months postoperatively), showing strong radial and ulnar digital pulses of all digits. CT angiography was repeated at 6 months postoperatively and showed graft occlusion. Despite this, no signs of critical ischemia developed, and clinical symptoms were still much improved from initial presentation, with only residual cold intolerance noted 13 months postoperatively. As an arterial graft donor site, the subscapular system is easily accessible, offers generous length, and provides for multiple branches, making it ideal for the reconstruction of large, complex arterial defects in the hand.